REEDUCATION FUNCTIONAL OF BREATHING IN THE CLIENT SUBMITTED TO GASTRECTOMY: PRE AND POSTOPERATIVE INTERVENTION PROGRAM - Eduardo Soares; Salete Soares (Revista Portuguesa de Enfermagem de Reabilitação, 2018)
Aim: To analyze the effects of a pre and post-operative breathing functional reeducation program in pain, respiratory rate and O2 saturation in the health/illness transition process of the client submitted to an elective gastrectomy.